Effects of shot peening on short crack growth rate and resulting low cycle fatigue behaviour in low pressure turbine blade material. (1st July 2013) - He, B Y; Soady, K A; Mellor, B G; Morris, A; Reed, P A S
Abstract : The effect of shot peening on subsequent low cycle fatigue behaviour of a representative low pressure steam turbine blade material has been investigated in bend test samples. An analysis of the short fatigue crack growth behaviour has been conducted. For samples with no stress concentration feature, shot peening was found to have a more evident beneficial effect at lower strain levels than at higher strain levels, whereas for samples with a stress concentration feature, the beneficial effect was retained even at higher strain levels. Preexisting cracks were observed on the shot peened surface, which started to grow at 10-25% of fatigue life in the low cycle fatigue regime. The crack propagation rate was slower than that observed in the ground sample, suggesting that the shot peening process delayed crack propagation. This improvement in fatigue life has been attributed to the significant slowing of small cracks while growing through surface regions of significant compressive residual stresses and local workhardening developed by the shot peening process. Once cracks in the notch root have penetrated this region in the depth direction, faster crack growth rates, similar to those observed in the ground case, were seen.